UBE2T silencing suppresses proliferation and induces cell cycle arrest and apoptosis in bladder cancer cells - Gong, Yan Qing (Oncol Lett, 2016)
Ubiquitin-conjugating enzyme E2T (UBE2T), a member of the ubiquitin-conjugating E2 family in the ubiquitin-proteasome pathway, has been reported to be overexpressed in certain tumor types and to have an important role in the Fanconi anemia pathway. In the present study, the expression of UBE2T and its association with bladder cancer were investigated; to the best of our knowledge, this has not been reported previously. Immunohistochemistry and western blot analysis demonstrated that UBE2T was significantly upregulated in bladder cancer tissues and cell lines compared with adjacent normal bladder tissues and a normal human urinary tract epithelial cell line, respectively. UBE2T was detectable in the nuclei and cytoplasm of cancer cells, exhibiting stronger expression in the nuclei. A UBE2T-siRNA-expressing lentivirus was constructed and used to infect human bladder cancer 5637 cells, in order to examine the role of UBE2T in bladder cancer cell growth in vitro. The knockdown of UBE2T significantly decreased bladder cancer cell proliferation and colony formation. Furthermore, UBE2T silencing induced cell cycle arrest at G2/M phase and increased cell apoptosis. Therefore, UBE2T serves an important role in the growth of bladder cancer cells, and may be considered as a potential biomarker and therapeutic target for bladder cancer.